Characterization of surface plasmon resonances in metallic planar nanostructures by electron energy loss spectroscopy - Bellido Sosa, Edson Pazur (My University, 2017)
Surface plasmon resonances at the nanoscale hold great potential for applications in many areas, and the characterization of plasmonic nanostructures plays a critical role in the realization of these applications. Electron energy loss spectroscopy (EELS) has emerged as a powerful characterization tool to study the response of plasmonic nanostructures due to its high spatial-resolution and the capability to probe bright as well as dark plasmonic modes. The main limiting factor of EELS is the energy resolution. However, in this thesis, we overcome this limitation using a combination of electron monochromation and the use of the Richardson-Lucy algorithm. We show that the algorithm could be used to obtain effective energy resolutions up to 10 meV. Using EELS we analyze the resonances of planar nanostructures, and we found that the supported resonances can be described as edge and cavity or film modes, behaving as 1D and 2D modes respectively. We also demonstrate that edge modes are unaffected by the presence of bends up to the critical angle of 90◦ where the modes start self-interacting producing large energy shifts. The interaction of plasmon resonances is also studied, and we show that the coupling can be reduced to three behaviors: coupling through the edge, coupling through a corner, and non-coupling. We propose a method to control the coupling through the edge in offset nanowires, by tuning the nodal alignment and spectral overlap of the edge modes. Finally, we analyze the plasmon modes supported by Koch snowflake fractal antennas, and we demonstrate that modes present in the fractals are formed by the edge modes supported by their characteristic edges. This thesis provides a complete picture of the surface plasmon resonances supported by planar nanostructures and demonstrates the ability of EELS to probe and image a wide variety of plasmonic resonances.
Keywords: Surface Plasmons, electron microscopy, EELS, Coupling, planar nanostructures